POSTINFECTIOUS OBLITERANS BRONCHIOLITIS IN CHILDREN - E. V. Boitsova; D. Yu. Ovsyannikov (LLC "Diagnostics and Vaccines", 2015)
Literature review describes the problem of bronchiolitis obliterans in children. The review analyzes modern date on etiology, morphological sings, clinical course, treatment and prognosis of diseas. The modern capabilities of diagnosis based on chest X-ray, computed tomography and pulmonary function testing are discussed.